2009
DOI: 10.1002/mana.200910842
|View full text |Cite
|
Sign up to set email alerts
|

Numerical integration and discrepancy, a new approach

Abstract: The paper deals with two closely related topics: (i) Numerical integration of functions belonging to SobolevBesov spaces with dominating mixed smoothness in cubes. (ii) Discrepancy measured in terms of Lebesgue and Sobolev-Besov spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…There are also known lower and upper bounds for the S r p,q B-discrepancy in arbitrary dimensions. Triebel, who initiated the study of the local discrepancy in other spaces such as the Besov spaces and Triebel-Lizorkin spaces of dominating mixed smoothness in [31] and [32], showed that for all 1 ≤ p, q ≤ ∞ and r ∈ R satisfying 1 p − 1 < r < 1 p and q < ∞ if p = 1 and q > 1 if p = ∞ there exists a constant c 1 > 0 such that for any N ≥ 2 the local discrepancy of any N-element point set P in [0, 1) s satisfies…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
“…There are also known lower and upper bounds for the S r p,q B-discrepancy in arbitrary dimensions. Triebel, who initiated the study of the local discrepancy in other spaces such as the Besov spaces and Triebel-Lizorkin spaces of dominating mixed smoothness in [31] and [32], showed that for all 1 ≤ p, q ≤ ∞ and r ∈ R satisfying 1 p − 1 < r < 1 p and q < ∞ if p = 1 and q > 1 if p = ∞ there exists a constant c 1 > 0 such that for any N ≥ 2 the local discrepancy of any N-element point set P in [0, 1) s satisfies…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
“…Apart from the L p -norms, until recently there was little done for other norms. In [17] and, in particular, in the forthcoming book [18] Triebel promoted the study of the discrepancy function in other function spaces such as suitable Sobolev, Besov or Triebel-Lizorkin spaces to gain more insight into its behavior and into applications to numerical integration. It is the purpose of this note to prove the conjectures in [18] concerning optimal upper bounds for the norm of the discrepancy function in Besov spaces of dominating mixed smoothness in the twodimensional case.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, optimality can be shown in Besov spaces of dominating mixed smoothness for certain parameter values, as these can be characterized by an equivalent norm via Haar coefficients, see [37,94,95]. For generalizations to higher dimensions, see [58,59].…”
Section: Example: Error Analysis Of Qmc With Hammersley Point Setsmentioning
confidence: 97%